Neurofilament Light Chain as a Biomarker for Cognitive Decline in Parkinson Disease - Aamodt, Whitley W.; Waligorska, Teresa; Shen, Junchao; Tropea, Thomas F.; Siderowf, Andrew; Weintraub, Daniel; Grossman, Murray; Irwin, David; Wolk, David A.; Xie, Sharon X.; Trojanowski, John Q.; Shaw, Leslie M.; et al. (Movement disorders, 2021)
ABSTRACT Background Neurofilament light chain protein (NfL) is a promising biomarker of neurodegeneration. Objectives To determine whether plasma and CSF NfL (1) associate with motor or cognitive status in Parkinson's disease (PD) and (2) predict future motor or cognitive decline in PD. Methods Six hundred and fifteen participants with neurodegenerative diseases, including 152 PD and 200 healthy control participants, provided a plasma and/or cerebrospinal fluid (CSF) NfL sample. Diagnostic groups were compared using the Kruskal−Wallis rank test. Within PD, cross‐sectional associations between NfL and Unified Parkinson's Disease Rating Scale Part III (UPDRS‐III) and Mattis Dementia Rating Scale (DRS‐2) scores were assessed by linear regression; longitudinal analyses were performed using linear mixed‐effects models and Cox regression. Results Plasma and CSF NfL levels correlated substantially (Spearman r = 0.64, P < 0.001); NfL was highest in neurocognitive disorders. PD participants with high plasma NfL were more likely to develop incident cognitive impairment (HR 5.34, P = 0.005). Conclusions Plasma NfL is a useful prognostic biomarker for PD, predicting clinical conversion to mild cognitive impairment or dementia. © 2021 International Parkinson and Movement Disorder Society